2019
DOI: 10.3389/fnbeh.2019.00186
|View full text |Cite
|
Sign up to set email alerts
|

Encoding Pleasant and Unpleasant Expression of the Architectural Window Shapes: An ERP Study

Abstract: The evaluation of building facades is one of the most important elements in built environments for helping architects and professionals to develop future designs. The form or shape of windows in building facades has direct impacts on perceivers’ affective state and emotions. To understand the impacts of geometric windows on the subject’s feedback and cortical activity, psychophysics experiments and electroencephalogram (EEG) recordings were measured from the participants. Our behavioral results show a distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Their behavioral results showed that rectangular, square, circular and semi-circular arches were considered as pleasant window shapes, while windows with triangle and triangular arches were determined as unpleasant. Regarding ERP results, the authors found that the effect of pleasant stimuli was larger in the left hemisphere than that of unpleasant ones ( Naghibi Rad et al, 2019 ), consistent with previous notions of lateralization with regards to emotional processes ( Dimond and Farrington, 1977 ; Reuter-Lorenz and Davidson, 1981 ; Canli et al, 1998 ). By using physiological sensors, such as EEG, Galvanic Skin Response (GSR), and eye-tracking (ET), Shemesh et al (2021) examined the connection between geometrical aspects of architectural spaces (such as scale, proportion, protrusion, and curvature) and the user’s emotional state in expert and non-expert participants (designers and non-designers, respectively).…”
Section: Neuro-architecture Research Methods Findings and Limitationssupporting
confidence: 83%
See 1 more Smart Citation
“…Their behavioral results showed that rectangular, square, circular and semi-circular arches were considered as pleasant window shapes, while windows with triangle and triangular arches were determined as unpleasant. Regarding ERP results, the authors found that the effect of pleasant stimuli was larger in the left hemisphere than that of unpleasant ones ( Naghibi Rad et al, 2019 ), consistent with previous notions of lateralization with regards to emotional processes ( Dimond and Farrington, 1977 ; Reuter-Lorenz and Davidson, 1981 ; Canli et al, 1998 ). By using physiological sensors, such as EEG, Galvanic Skin Response (GSR), and eye-tracking (ET), Shemesh et al (2021) examined the connection between geometrical aspects of architectural spaces (such as scale, proportion, protrusion, and curvature) and the user’s emotional state in expert and non-expert participants (designers and non-designers, respectively).…”
Section: Neuro-architecture Research Methods Findings and Limitationssupporting
confidence: 83%
“…As there are too many studies in this area to report in detail [for an overview see Higuera-Trujillo et al (2021) ], the following exemplary studies suffice to provide the reader with a broad sense of the research questions and imaging methods used in this field. For example, using EEG in a psychophysics experiment, Naghibi Rad et al (2019) investigated the impact that window shapes in building facades had on the perceivers’ emotional state and cortical activity. Their behavioral results showed that rectangular, square, circular and semi-circular arches were considered as pleasant window shapes, while windows with triangle and triangular arches were determined as unpleasant.…”
Section: Neuro-architecture Research Methods Findings and Limitationsmentioning
confidence: 99%
“…For instance, utility, familiarity and/or hedonism might be factors that contribute to generally preferring common-use objects with curved contours over sharp-angled ones ( Bar & Neta, 2006 ; Bar & Neta, 2007 ; Munar et al, 2015 ). Preference for curvature was shown using drawings of car interiors ( Leder & Carbon, 2005 ), pictures of windows ( Naghibi Rad et al, 2019 ), furniture ( Dazkir & Read, 2012 ), product packaging ( Westerman et al, 2012 ), exterior façades ( Ruta et al, 2019 ) and interior architectural environments ( Van Oel & Van den Berkhof, 2013 ; Vartanian et al, 2013 ; Vartanian et al, 2017 ), among others. While most of these stimuli involve representational content, preference for curvature was also found using non-representational art-related stimuli such as abstract artworks ( Ruta et al, 2021 ) or abstract shapes and patterns ( Bertamini et al, 2016 ; Bertamini et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This category includes seven studies exploring the effects of specific environmental characteristics that were designed in a laboratory setting by using different measurement tools, four of these studies used EEG as the main brain measurement tool and stimuli were also presented in the form of both images and videos. Naghibi Rad et al (2019) employed EEG to investigate the subjects’ emotional response to geometrical window shapes of building facades marked as either pleasant or unpleasant (Naghibi Rad et al, 2019). In another study, Hakak et al (2016) simulated some videos of architectural environments as stimuli to investigate different perceptions of the spatial environments and their influence on the precentral gyrus by concentrating on three different categories of environments (fully designed, semi-designed, and abstract designed; Hakak et al, 2016).…”
Section: Resultsmentioning
confidence: 99%